Analysis of Functional Suitability and Usability in Sales Order Procedure to Determine Management Information System Quality - Ariyani, Sri; Sudarma, Made; Wicaksana, Putu Aryasuta (Universitas Nusantara PGRI Kediri, 2021)
In the development of information systems, it is very important to pay attention to the quality of the system which can be reviewed through aspects of usability for its users and following the needs and specifications of its users. This study will analyze the quality of the sales order management information system based on two characteristics of the ISO 25010 quality standard system, namely functional suitability and usability. The functional suitability test was carried out by the BlackBox testing method to test three sub-characteristics of functional suitability that are functional completeness, functional correctness, and functional appropriateness. Usability tests use a use questionnaire which is divided into four criteria that are usefulness, ease of use, ease of learning, and satisfaction. In testing the suitability of functionality involving 5 respondents and 17 respondents in usability testing. The results of this study indicate that the sales order management system fulfills two characteristics of information system quality that are functional suitability and usability. Where all the features designed are by the successful features, and the usability characteristics are 85.45% which indicates that the system is very feasible to implement.